Censura y edición póstuma de la obra de Hipólita de Rocabertí: a propósito de unos poemas manipulados. - ZARAGOZA GÓMEZ, VERÒNICA (Scripta, 2016)
The goal of this paper is to examine certain aspects of the publishing process of the work of the Catalan Dominican nun Hipólita de Rocabertí from an original philological perspective through the edition and analysis of three of her poems, which were published in the Tratado dividido en quatro libros. El primero contiene: la exposición literal y mística de los psalmos penitenciales; el segundo, la preparación para la muerte; el tercero, coloquios del alma christiana con Dios; el quarto, fundamento sólido de la oración por ser todo fundado en el santo Evangelio (Valencia, Jaime de Bordázar, 1683) and which present a complex textual transmission, given that some of them were modiied in various editions. By comparing the different testimonies of the compositions that we edit, we intend to provide new interpretative materials, which might contribute to a better understanding of the building process of the image of the author's holiness in the XVII century, in the new framework of the post-tridentine catholic reform.